Enough Already! A Socialist Feminist Response to the Re-emergence of Right Wing Populism and Fascism in Media - Agostinone-Wilson, Faith (Critical Media Literacies Series, 2020)
This text analyses the rapid rise of global authoritarian populism and fascism and how these movements incorporate misogyny into their ideologies within and beyond social media. Readership: Readership includes those interested in critical, Marxist, and feminist analyses of the role of media in the rise of authoritarian populism and fascism, within the context of recent political events.